Aggression as a form of adaptation in conflicting relationships parents – teenagers - Sandu, Mihaela Luminița; Ciubuc, Georgiana Adelina (Technium Social Sciences Journal, 2023)
This paper aims to present the main theoretical aspects of aggressiveness as a form of adaptation in the parent-teenager relationship, given the different characteristics of adolescents, but also of parents. Aggressiveness is an attribute characterized by a whole series of manifestations in an intentional or not intentional manner, which can be manifested in social groups, in the school environment, or even in the family. This paper comes with a unique perspective from two categories of subjects, namely, adolescents and parents from urban areas and adolescents and parents from rural areas, who have a different educational level, belonging to different social backgrounds, regarding aggression as a personality trait, how it may or may not be influenced by self-esteem or dysfunctional negative emotions.